Performance evaluation using hybrid glowworm swarm-Pareto optimization in the smart communication system. (October 2022) - Yadav, Kusum; Al-Dhlan, Kawther A.
Abstract: The Wireless Sensor Network (WSN) is described as a combination of sensor nodes that are installed in close proximity to one another in specific circumstances. Different research work is carried out for data sharing in the area of WSN and it cannot adapt to the network in the real-time network because of its characteristics. If the cluster head is selected without bothering the availability of resources, it results in network failure. Due to this, there will be more loss of packet and violation of security when they transfer the data collected from the cluster to the sink node which is a problem and still research is done in this area. Authentication is done to guarantee security among the CH and the sink/base station, and the base station must authenticate the CH. After the authentication task is completed, the data is transmitted. The main intent of the proposed scheme is to attain effective transmission and QoS by utilizing optimal node selection. Based on the findings of the simulation trials, the suggested approach outperformed the previous research studies.